Transition properties among Ω states originating from X 2Π, A 2Σ+, B 2Π, C 2Σ+, a 4Π, b 4Σ+, c 4Δ, and d 4Σ– states of SiP molecule. (September 2021) - Wu, Min; Zhu, Zunlue
Highlights: Lifetimes are 93 – 254 and 23.9 – 30.3 µs for the c 4 Δ and d 4 Σ – states, respectively. Lifetimes are 410 – 1044 and 380 – 906 µs for the B 2 П1/2 and B 2 П3/2 states, respectively. Lifetimes are 0.27 – 66 and 1.5 – 2.38 × 10 4 ms for the A 2 Σ + and b 4 Σ + states, respectively. Emissions from the C 2 Σ + 1/2 to the X 2 П3/2, X 2 П1/2, and A 2 Σ + 1/2 states were the strongest. Lifetimes are 0.95 – 1.31 µs for the C 2 Σ + 1/2 state. Abstract: The potential energy curves of X 2 Π, A 2 Σ +, B 2 Π, C 2 Σ +, a 4 Π, b 4 Σ +, c 4 Δ, and d 4 Σ – states of SiP molecules and the transition dipole moments of the transitions between these states were calculated using the CASSCF method, followed by the icMRCI approach. The radiative lifetimes of the first 16 vibrational levels were 0.27 – 66 and 1.5 – 2.38 × 10 4 ms for the A 2 Σ + and b 4 Σ + states, respectively. Those were 146 – 497, 93 – 254, 23.9 – 30.3, and 0.85 – 1.1 µs for the B 2 Π, c 4 Δ, d 4 Σ –, and C 2 Σ + states, rspectively. The spin–orbit coupling constants of the X 2 Π, B 2 Π, a 4 Π, and b 4 Σ + states were evaluated. Including the spin–orbit coupling effect, the radiative lifetimes of the A 2 Σ + 1/2, B 2 П1/2, B 2 П3/2, C 2 Σ + 1/2, a 4 П–1/2, a 4 П1/2, a 4 П3/2, a 4 П5/2, b 4 Σ + 1/2, and b 4 Σ + 3/2 states were calculated. The lifetimes of the first 16 levels were 0.35 – 0.42, 3.1 – 5.5, 1.3 – 5.8, and 30 – 57 s for the a 4 П–1/2, a 4 П1/2, a 4 П3/2, and a 4 П5/2 states, respectively. And those were 2.3 – 268 and 2.6 – 257 ms for the b 4 Σ + 1/2 and b 4 Σ + 3/2 states, respectively. The SOC effect made the radiative lifetimes of the A 2 Σ +, B 2 Π, and C 2 Σ + states become longer. Among the spontaneous emissions between these Ω states, those from the C 2 Σ + 1/2 state to the X 2 П3/2, X 2 П1/2, and A 2 Σ + 1/2 states were the strongest. The results indicated that the strong emissions originated from the lower levels of the C 2 Σ + 1/2 state. Furthermore, almost all of these strong emissions were in the visible region. All emissions generating from the a 4 П–1/2, a 4 П1/2, a 4 П3/2, and a 4 П5/2 states are extremely weak. The radiative–lifetime distribution of each level υ versus the rotational quantum number J was evaluated for several Ω states. Graphical abstract: Image, graphical abstract